Associations Between the Molecular and Optical Properties of Dissolved Organic Matter in the Florida Everglades, a Model Coastal Wetland System - Wagner, Sasha; Jaffé, Rudolf; Cawley, Kaelin; Dittmar, Thorsten; Stubbins, Aron (Frontiers in Chemistry, 2015)
Optical properties are easy-to-measure proxies for dissolved organic matter (DOM) composition, source and reactivity. However, the molecular signature of DOM associated with such optical parameters remains poorly defined. The Florida coastal Everglades is a subtropical wetland with diverse vegetation (e.g., sawgrass prairies, mangrove forests, seagrass meadows) and DOM sources (e.g., terrestrial, microbial and marine). As such, the Everglades is an excellent model system from which to draw samples of diverse origin and composition to allow classically-defined optical properties to be linked to molecular properties of the DOM pool. We characterized a suite of seasonally- and spatially-collected DOM samples using optical measurements (EEM-PARAFAC, SUVA254, S275-295, S350-400, SR, FI, freshness index and HIX) and ultrahigh resolution mass spectrometry (FTICR-MS). Spearman’s rank correlations between FTICR-MS signal intensities of individual molecular formulae and optical properties determined which molecular formulae were associated with each PARAFAC component and optical index. The molecular families that tracked with the optical indices were generally in agreement with conventional biogeochemical interpretations. Therefore, although they represent only a small portion of the bulk DOM pool, absorbance and fluorescence measurements appear to be appropriate proxies for the aquatic cycling of both optically-active and associated optically-inactive DOM in coastal wetlands.